Debates on conservation and protected areas: consolidated paradigms and new horizons - D'Amico, María Paula (2015)
This article briefly analyzes the main theoretical discussions on nature conservation through protected areas. In a context of expansion and diversification of mechanisms to protect nature, such strategy stresses due to its precursor character and the magnitude and intensity of their territorial consequences. Initially, we address the consolidated paradigms over nature conservation. On one hand, fortress conservation supports the idea of parks and natural reserves without humans. On the other, for community based conservation there is no need to evict or expel communities to achieve conservation goals. Without ignoring the uneven impacts that this two paradigms implies, both shows a moral condition over nature conservation and besides their differences are reduced on management terms. Aimed at broadening the analysis, we point out theoretical frames that explain conservation and their mechanisms within capitalism and are especially interested in unraveling the characteristics and dynamics assumed in the current neoliberal phase. Thus, conservation is a social issue where a diversity of interests converges rather than a simple concern about protecting nature.